The Character of Influenza Virus the H7 Subtype and Alert to Novel Influenza Virus H7N9 Subtype Virus - NLP Indi Dharmayanti; Bahri S (Indonesian Center for Animal Research and Development, 2013)
Influenza virus subtype H7 influenza viruses as well as other influenza virus geographically divided into two distinct genetic lineages, North American (H7N2, H7N3) or Eurasian (H7N7 and H7N3). Unlike the AI virus subtypes H5, since 1997 until now, all the infections caused by the H5 virus has Neuraminidase subtype 1 but H7 subtype of AI virus that transmitted successfully to humans have variety of Neuraminidase, so it seems compatible with H7 subtype. In poultry, the H7 subtype of AI virus typically causes mild symptoms, although there are also several outbreaks caused by this subtype virus, so it did not cause panic and active surveillance activities to identify this virus. It is very different from the H5N1 virus which caused many deaths and losses in poultry that infected with H5N1 virus so that it can be identified quickly. In April 2013, China reported a new AI virus is novel H7N9 which resulted in several people died. The world became aware of the H7N9 virus spreading to outside from China, it takes vigilance to be able to anticipate the disease, including Indonesia. Analysis of novel H7N9 virus showed that all genes of the virus is of avian origin, and the three other genes of the virus are reassorment from six internal genes of the AI virus A (H9N2) A/brambling/Beijing/16/2012, HA gene derived from A/duck/Zhejiang/12/2011 (H7N3), and NA genes thought to have come from A/wildbird/Korea/A14/2011 (H7N9). Epidemiological studies show that 77% of people infected by H7N9 have direct or indirect contact with animals including poultry when visiting or working in live poultry markets. Novel H7N9 virus was also found in pigeons, chickens, and environmental that have high genetic similarities with the novel H7N9 virus that infects humans. Until now (May 2013), a novel H7N9 virus has not been identified in Indonesia, so as a precaution and because the symptoms caused by the H7N9 virus is not visible (mild symptom) in poultry so that the necessary actions as follows: 1) Active surveillance (market traditionally, backyard chicken including pigeons), 2) Updating method of diagnosis, and 3) The study of human-animal interface, and 4) the study of AI complete virus genome to detect novel influenza viruses, including influenza H7N9 novel virus. Key words: Subtype H7 of Avian Influenza virus, China, novel H7N9, virus reassortant